Quantum Mechanical Predictions of the Antioxidant Capability of Moracin C Isomers - Parise, Angela; De Simone, Bruna Clara; Marino, Tiziana; Toscano, Marirosa; Russo, Nino (Frontiers in Chemistry, 2021)
The antioxidant capability of moracin C and iso-moracin C isomers against the OOH free radical was studied by applying density functional theory (DFT) and choosing the M05-2X exchange-correlation functional coupled with the all electron basis set, 6-311++G(d,p), for computations. Different reaction mechanisms [hydrogen atom transfer (HAT), single electron transfer (SET), and radical adduct formation (RAF)] were taken into account when considering water- and lipid-like environments. Rate constants were obtained by applying the conventional transition state theory (TST). The results show that, in water, scavenging activity mainly occurs through a radical addition mechanism for both isomers, while, in the lipid-like environment, the radical addition process is favored for iso-moracin C, while, redox- and non-redox-type reactions can equally occur for moracin C. The values of pKa relative to the deprotonation paths at physiological pH were predicted in aqueous solution.